2015
DOI: 10.1186/s13028-015-0109-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recording of pericarditis and lung disorders at routine meat inspection with findings at systematic health monitoring in Danish finisher pigs

Abstract: BackgroundThe use of secondary data is widespread in a range of surveillance and monitoring applications because of the low cost and high availability associated with this form of data. However, as they are often collected for quite unrelated purposes, they are not necessarily fit for the new purpose that is required of them. Routine meat inspection data were originally collected with the purpose of safeguarding food, but have been re-tasked to also include animal welfare assessment. The objective of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 5 publications
3
23
2
Order By: Relevance
“…Both publications particularly discuss pericarditis. Nielsen et al (2015) conclude that there is not a strong correlation between the post mortem findings and the prevalence assessed on the basis of systematic health monitoring in fattening pigs in Denmark. Raji et al (2010) found a relatively high prevalence (17.06 %) in cattle in an abattoir in Nigeria.…”
Section: Zoonotic Diseasementioning
confidence: 71%
See 1 more Smart Citation
“…Both publications particularly discuss pericarditis. Nielsen et al (2015) conclude that there is not a strong correlation between the post mortem findings and the prevalence assessed on the basis of systematic health monitoring in fattening pigs in Denmark. Raji et al (2010) found a relatively high prevalence (17.06 %) in cattle in an abattoir in Nigeria.…”
Section: Zoonotic Diseasementioning
confidence: 71%
“…Cardiac pathology is specifically investigated during meat inspection (Nielsen et al, 2015, Raji et al, 2010. Both publications particularly discuss pericarditis.…”
Section: Zoonotic Diseasementioning
confidence: 99%
“…The main practical limitation of the study was the line speed (6 pigs/min), placing a time constraint on the assessment of lung lesions in each pig. Nielsen et al (2015) found a moderate correlations between lung lesions recorded at routine meat inspection and lung lesions recorded at systematic health monitoring. Differences in observer sensitivity and the differing objectives of public health versus animal health monitoring may explain why the results of our study are different from those of Teixeira et al (in preparation) who found significant Epidemiology and control of hazards in pork production chain -SAFEPORK One health approach under a concept of farm to fork associations between tail lesion scores and lung condemnations due to pleurisy and (pleuro)pneumonia.…”
Section: Discussionmentioning
confidence: 84%
“…Differences exist between findings made by meat inspectors or pathologists/veterinary researchers, with the latter typically showing higher sensitivity [21,[25][26][27], which is probably due to different roles and responsibilities and the associated time constraints.…”
Section: Continued Training Of Personnel and Standardization Of MI Damentioning
confidence: 99%